PCR Cloning Combined With DNA Barcoding Enables Partial Identification of Fish Species in a Mixed-Species Product - Silva, Anthony J.; Kawalek, Michael; Williams-Hill, Donna M.; Hellberg, Rosalee S. (Frontiers in Ecology and Evolution, 2020)
DNA barcoding is a valuable tool for regulatory identification of fish species; however, it does not perform well when multiple species are present within the same food product. Therefore, the objective of this study was to examine the use of PCR cloning to identify fish in a mixed-species product that cannot be identified with standard DNA barcoding. A total of 15 fish ball mixtures were prepared with known amounts of Nile tilapia (Oreochromis niloticus), Pacific cod (Gadus macrocephalus), and walleye pollock (Gadus chalcogrammus). Three subsamples from each fish ball underwent DNA extraction, full DNA barcoding (655 bp), and mini-barcoding (226 bp) of the cytochrome c oxidase subunit 1 (CO1) gene. Subsamples that did not pass sequencing according to regulatory standards were further analyzed with PCR cloning. All fish balls made of just one species tested positive for that species (i.e., tilapia, cod, or pollock) with both full and mini-barcoding. However, only tilapia was detected in fish balls containing multiple species when tested with standard barcoding techniques, reflecting an inaccurate representation of the fish mixture and suggesting species bias. PCR cloning allowed for identification of Pacific cod in 86% of the mixed-species fish balls tested with full-barcode cloning and 100% of the mixed-species fish ball tested with mini-barcode cloning. However, PCR cloning did not enable the identification of walleye pollock. Standard full barcoding produced more high quality sequences compared to mini-barcoding yet failed to accurately detect all species present in the tested fish mixtures. Overall, the results of this study show that PCR cloning may be an effective method to identify certain fish in mixed-species products when standard DNA barcoding fails. However, additional research is needed to overcome the species bias observed in this study.